A comparison of the effectivity between unwaxed dental floss and commercially available sewing thread in the removal of dental plaque - Dujunco, Myra Rebecca
A study to compare the effectivity between unwaxed dental floss and commercially available sewing thread was conducted utilizing 5 UPCD senior clinicians as subjects. To determine this, a Microbial colony count of samples obtained before and after flossing or threading was performed. The designated test area is the buccal embrasure between the maxillary second premolar and the maxillary first molar. Floss was used for the right side in all the subjects and thread on the left side. The test area was swabbed with a sterile cotton swab before and after flossing or threading. The cotton swabs were cultured in Brain Heart Infusion media and incubated for 3 hours. The sample is diluted with NSS to a concentration of 1:10,000. 1.0 ml. of this diluted sample was placed in a petri dish and nutrient agar was added. The dishes were incubated for 24 hours afterwhich the colonies were counted. Because of the small sample size used, a statistical non=parametric test was employed to analyze the date. For the purpose to the study, the sign test was utilized. The results obtained shows while that of the floss is effective in removing interdental plaque, thread shows great potential in it's ability to remove interdental plaque. However, this conclusion can only be applied to the study. The researchers, therefore, suggest that similar studies be carried out utilizing larger sample pools to obtain more significant findings.